2017
DOI: 10.7205/milmed-d-16-00251
|View full text |Cite
|
Sign up to set email alerts
|

Thermoregulatory Response to Exercise After Exertional Heat Stroke

Abstract: Background: After one episode of exertional heat stroke (EHS), risk factors must be identified to determine the potential for subsequent episodes. One of these risk factors, core body temperature (T co ) kinetics during strenuous exercise, may be a surrogate marker suggestive of impaired thermoregulation. This study aimed to determine the kinetics of increases in T co among military subjects who had a history of EHS. Methods: Forty subjects (38 males, mean age 28.4 ± 4.9 years, mean body mass index 24.9 ± 2.4)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…Higher environmental temperatures further increase the risk. Thus, our present model fulfills that EHS is associated with excessive hyperthermia (over 40 °C Tco), encephalopathy, and confusion or coma during or just after strenuous physical activity in young, previously healthy subjects 17 . Indeed, in our rats, EHS occurs within the first 2 h of exertion and not necessarily at high ambient temperatures 18 .…”
Section: Discussionsupporting
confidence: 65%
“…Higher environmental temperatures further increase the risk. Thus, our present model fulfills that EHS is associated with excessive hyperthermia (over 40 °C Tco), encephalopathy, and confusion or coma during or just after strenuous physical activity in young, previously healthy subjects 17 . Indeed, in our rats, EHS occurs within the first 2 h of exertion and not necessarily at high ambient temperatures 18 .…”
Section: Discussionsupporting
confidence: 65%
“…Heat stroke may cause abnormal function in multiple organs. The major cause for MODS is an uncontrolled thermoregulatory response to exercise after an episode of exertional heat stroke (13). Dysfunction of the intestinal barrier may be caused by heat stroke and may lead to increased intestinal permeability (14).…”
Section: Discussionmentioning
confidence: 99%
“…A score below 35 represents those who are likely to experience heat intolerance while those who score above a 75 are considered heat acclimated [16]. Studies performed by Armstrong [60,61], which replicated Shvartz's [16] work, demonstrated high variability in composite score outcomes. Additionally, due to the high cardiorespiratory fitness level of Armstrong's volunteers, individuals were able to achieve low HR scores on the first day which therefore increased the composite score supporting the concept that composite score ratings can be misleading as a result of the population tested.…”
Section: Idf's Methods Of Determining Heat Intolerancementioning
confidence: 99%